The current status and future prospects of comparative studies in Chinese and Western art - Yuliang, Yang; Omar, Mohd Adzman; xiao, Feng (Journal of Islamic, Social, Economics and Development, 2025)
Since the Age of Sail, and especially under 21st-century globalisation, exchanges between Chinese and Western art have intensified, fostering mutual influence in concepts and practices and sparking a global artistic dialogue. Contemporary artists, engaging with both tradition and cultural collision, increasingly adopt cross-cultural creation. In this context, comparative studies of Chinese and Western art hold dual significance: deepening understanding of distinct aesthetic systems and enriching the concept of “beauty,” while promoting cultural exchange and the evolution of new artistic ideas. This study examines Chinese and Western art from 2022 to 2025, focusing on four dimensions—technique, aesthetics, art philosophy, and art education. Using a literature review approach, it analyses high-quality SSCI, AHCI, and SCOPUS-indexed journal articles to map recent academic achievements, assess the current state of comparative research, and anticipate future trends. The discussion is structured as follows: (1) differences and integration in artistic techniques; (2) the evolution of aesthetic concepts; (3) comparative values in art philosophy; (4) current and prospective developments in art education; and (5) concluding remarks with future research directions.